2002
DOI: 10.1002/polb.10204
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical behavior of acrylonitrile butadiene rubber/poly(ethylene‐co‐vinyl acetate) blends

Abstract: The dynamic mechanical behavior of uncrosslinked (thermoplastic) and crosslinked (thermosetting) acrylonitrile butadiene rubber/poly(ethylene-co-vinyl acetate) (NBR/EVA) blends was studied with reference to the effect of blend ratio, crosslinking systems, frequency, and temperature. Different crosslinked systems were prepared using peroxide (DCP), sulfur, and mixed crosslink systems. The glass-transition behavior of the blends was affected by the blend ratio, the nature of crosslinking, and frequency. sThe dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…This might also suggest the distribution of size or amount of EVA crystallite is similar in these blends. A few studies have also noted similar observation in rubber/plastic blends (Varghese et al, 2002, Saleesung et al, 2010. Study conducted by Ratnam et al (2014) concluded the presence of ground tire rubber in EVA matrix has a disrupting role in the EVA chain molecules arrangement when cooling from melt, thus reducing the crystallinity of the blend.…”
Section: Dsc Analysismentioning
confidence: 76%
“…This might also suggest the distribution of size or amount of EVA crystallite is similar in these blends. A few studies have also noted similar observation in rubber/plastic blends (Varghese et al, 2002, Saleesung et al, 2010. Study conducted by Ratnam et al (2014) concluded the presence of ground tire rubber in EVA matrix has a disrupting role in the EVA chain molecules arrangement when cooling from melt, thus reducing the crystallinity of the blend.…”
Section: Dsc Analysismentioning
confidence: 76%
“…are used in many demanding applications where the properties of thermal stability and fire resistance are priorities and therefore have been extensively studied [1][2][3][4]. Polymer blending has been reported to have great impact on the thermal stability of polymers [5][6][7][8][9][10][11][12][13]. Compatibility between two components in a binary blend is one of the decisive factors, which determines the thermal stability of polymer blends [14][15][16][17][18][19], and therefore compatibilisation has profound effect on the thermal stability of polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…The damping properties of the blends increased with NBR content. 19 Recently in another work, Thomas et al have reported the effect of blending ratio, reactive compatibilization, and dynamic vulcanization of high-density polyethylene (HDPE)/EVA blends. 20 Sethi et al have investigated the dynamic mechanical properties of nonirradiated and irradiated blends of low-density polyethylene and ethylene vinyl acetate copolymer blends.…”
mentioning
confidence: 99%